2006
DOI: 10.1017/s0021859606006216
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of vegetative filter strips in attenuating nutrient and sediment runoff from irrigated pastures

Abstract: Increasing concern about non-point source pollutants released from grazing livestock, a worldwide problem, motivated the present study on the effects of vegetative filter strips (VFS) for controlling pollutants (nutrients, micro-organisms and sediment loading) from grazed, irrigated pastures. Flood-irrigated pastures are an important source of forage for livestock during summer months in California, USA when the surrounding rangelands are dry and dormant. Significant amounts of runoff can be generated from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 17 publications
1
19
0
3
Order By: Relevance
“…A key parameter in this respect seems to be the extent of runoff convergence when entering buffer strips. Whenever surface runoff converges into buffer strips there is a reduction of the retention capacity of the VFS (Bach, Fabis, Frede, & Herzog, 1994a, 1994bDillaha et al, 1989;Dosskey, Helmers, Eisenhauer, Franti, & Hoagland, 2002;Hay, Pittroff, Tooman, & Meyer, 2006;LeedsHarrison et al, 1999;Verstraeten, Poesen, Gillijns, & Govers, 2006). Bach et al (1994a) pointed out the difficulties of linear structures, like plough furrows and ditches, leading to a reduced filter effect whenever concentrated surface flow enters buffer strips.…”
Section: Introductionmentioning
confidence: 99%
“…A key parameter in this respect seems to be the extent of runoff convergence when entering buffer strips. Whenever surface runoff converges into buffer strips there is a reduction of the retention capacity of the VFS (Bach, Fabis, Frede, & Herzog, 1994a, 1994bDillaha et al, 1989;Dosskey, Helmers, Eisenhauer, Franti, & Hoagland, 2002;Hay, Pittroff, Tooman, & Meyer, 2006;LeedsHarrison et al, 1999;Verstraeten, Poesen, Gillijns, & Govers, 2006). Bach et al (1994a) pointed out the difficulties of linear structures, like plough furrows and ditches, leading to a reduced filter effect whenever concentrated surface flow enters buffer strips.…”
Section: Introductionmentioning
confidence: 99%
“…Contaminant reduction also occurs through interception adsorption, infiltration, and degradation of pollutants dissolved in water (Hubbard et al 2003). Other researchers have reported on the effectiveness of vegetative buffers in treating agricultural runoff (Snyder et al 1998;Smith et al 2000;Bharati et al 2002;Gharabaghi et al 2001;Koelsch et al 2006) and consider them a best management practice for surface runoff pollutant removal (Dillaha et al 1989;Mickelson and Baker 1993;Gilley et al 2000;Lee et al 2000;Wang et al 2005;Hay et al 2006). Vegetative buffer studies also showed significant reductions of NO 3 -N, PO 4 -P, and total P in runoff (Patty et al 1997; Wenger et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These buffer strips provide erosionvia interception-adsorption, infiltration, and degradation of pollutants dissolved in water (Dillaha et al 1989). The VFS buffers are considered to be a best management practice that has been shown to reduce sediment and nutrient losses in a range of agricultural settings, including crop fields and feedlots (Dillaha et al 1985;Magette et al 1989;Mickelson and Baker 1993;Patty et al 1997;Lee et al 2000;Wang et al 2005;Hay et al 2006). These researchers also found that VFS buffers have potential for significantly improving the water quality of RO.…”
mentioning
confidence: 99%